Hubungan Antara Faktor Personal Dengan Perilaku Pemeriksaan Payudara Sendiri (Sadari) Pada Mahasiswi S1 Kesehatan Masyarakat Universitas Airlangga - Zahra Fatimah Yuniar; Mochammad Bagus Qomaruddin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Self-Breast Examination (BSE) is an activity to find out early information on breast cancer. Efforts to do BSE can reduce morbidity and mortality by up to 20%. The suggestion to do BSE works at a long time, which is 20 years and above. In general, someone will do BSE activities if they have adequate knowledge. Public health students at the age of 20 years and have sufficient knowledge to take preventative and promotion measures for the health of breast cancer problems. The purpose of this study was to analyze the relationship between personal factors (knowledge, attitude, cancer history and history of cancer) with BSE behavior. This research is a descriptive correlational study, using a cross sectional research design. The research sample consisted of 186 people, who were taken randomly using simple random sampling. Data analysis in this study is Chi-Square Test. The results showed that there was a relationship between attitudes (p = 0,023) with BSE behavior. Whereas between knowledge (p = 0,863), family breast cancer history (p = 0,591), and self-breast cancer history (p = 0,164) there was no correlation with BSE behavior.